Plasma bio-adrenomedullin is a marker of acute heart failure severity in patients with acute coronary syndrome - Arrigo, Mattia; Parenica, Jiri; Ganovska, Eva; Pavlusova, Marie; Mebazaa, Alexandre (International journal of cardiology. Heart & vasculature, 2019)
BACKGROUND: The assessment of acute heart failure (AHF) in patients with acute coronary syndrome (ACS) is challenging. This study tested whether measuring plasma adrenomedullin in patients admitted for ACS provides valuable information regarding the presence of AHF at admission or its occurrence during hospitalization. METHODS AND RESULTS: The study population consisted of 927 prospectively enrolled patients with ACS. Blood samples for the measurement of plasma bio-adrenomedullin (bio-ADM) were collected at admission. Patients with alveolar pulmonary edema and interstitial pulmonary edema on chest radiography at admission had stepwise higher plasma concentrations of bio-ADM compared to patients with no or mild pulmonary congestion: 54.3 ± 10.6 vs. 27.6 ± 2.1 vs. 22.5 ± 0.7 ng/L, overall P < 0.001. Patients with ACS complicated by AHF during the index hospitalization displayed higher plasma bio-ADM concentrations at admission compared to patients without AHF (33.8 ± 2.7 vs. 21.8 ± 0.7, P < 0.001): the higher the severity of AHF, the higher plasma bio-ADM concentrations at admission. Patients with cardiogenic shock displayed the highest values. Accordingly, bio-ADM concentrations at admission were associated with a higher risk of occurrence of AHF during index hospitalization (odds ratio 1.018, 95% confidence interval 1.011-1.026, P < 0.001). CONCLUSIONS: Plasma adrenomedullin is a marker associated with AHF severity in patients with ACS.
Keywords: Acute coronary syndrome; Pulmonary edema; Bio-adrenomedullin; Acute heart failure